Organizational cloud service adoption: a scientometric and content-based literature analysis - Haag, Steffi; Eckhardt, Andreas (Zeitschrift für Betriebswirtschaft, 2014)
This paper takes a scientometric research approach and undertakes a categorized literature analysis to provide a comprehensive and systemic overview of the current status of research on cloud services and their adoption by organizations. We review 52 journals and proceedings of the information systems field to identify and systematically categorize 36 articles on the topic. Our content-based analysis shows that the scarce theoretical and empirical work on organizational cloud service adoption has developed and explored factors that directly or indirectly drive organizations to adopt or inhibit them from adopting cloud services from different perspectives and dimensions. We classify these driving and inhibiting determinants based on the technology organization environment framework Tornatzky and Fleischer (The process of technological innovation. Lexington Books, Lexington, 1990) to provide a structured summary. Based on our analysis and recent cloud evolution in practice, we identify five new research areas, including theoretical and practical phenomena describing determinants and consequences of cloud service adoption in organizations: information technology (IT) related public threat appeals, trust in the technology versus trust in the vendor, bring your own cloud, transformation of organizational identity, and intelligent clusters of IT initiatives. For each phenomenon we provide relevant research questions, potential theoretical foundations, and methodologies to guide future research endeavors in this field.
Keywords: review; BYOC; organizational level; shadow sourcing